The Concept of Happiness in Aristotle’s Politics: A Reconstructive Adaptation for Contemporary Nigeria - Prince Nwinee TamBari; Francis Iroryakpo Igben (Jurnal Ilmu Sosiologi Dialektika Kontemporer, 2021)
The nature and character of the state are central to the enterprise of Aristotle’s political philosophy. His conception of politics is derived from, and influenced by, his firm belief in political realism, in which case, his idea of the state and political institutions is anchored and hinged on the understanding of political realities or actualities. Aristotle argues that the state is natural and conceives of it as a logical extension of the family. From his own perspective, the state is a unit writ large. This paper, therefore, examines the place of happiness in Aristotle’s politics, showing its implications for politics and governance in contemporary Nigerian body-politics. It looks at why the state was set up in the first place and how it fits into the modern Nigerian search for good governance. It adopts a qualitative research method, which is basically descriptive. It also employs the method of textual analysis using the matrix of hermeneutics. It serves as a blueprint for public policy with a view to enhancing good governance in Nigeria. It posits, in conclusion, that governance and its institutional agencies are meaningful to the extent that they promote citizens’ happiness through the instrumentality of state power. It recommends an adaptation of Aristotle’s concept of happiness as a theoretical construct to guide fundamental objectives and directive principles of state policies in contemporary Nigeria. It also recommends that state power be used as an apparatus for enhancing the common good of all Nigerians.